Environmental Stressors and Older Adult Morbidity: Initial Findings from University Medical Centre Maribor as Part of a Slovenian - Turkish Bilateral Study - Odabaş, Neşe; Dobnik, Mojca; Lorber, Mateja; Rozman, Urška; Tezel, Ayfer; Šostar Turk, Sonja; Lavrič, Miha (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
Environmental stressors such as air pollution and weather variability are increasingly recognized as important determinants of health in older adults, yet evidence on their short-term effects in Central Europe remains limited. This study examines associations between meteorological conditions, air pollution, and cardiovascular and respiratory morbidity among adults aged 65 years and older presenting to emergency departments in Slovenia. A retrospective observational analysis of emergency department visits in 2024 (N = 4,870) was conducted, linking ICD-10 diagnoses with daily meteorological and air pollution data (NO₂, PM₂.₅, PM₁₀, benzene) and analyzed using multivariable regression models adjusted for age, sex, and season. Cardiovascular disease prevalence was primarily age-driven, whereas respiratory morbidity showed clear seasonal patterns and significant associations with NO₂, particularly during the cold season, with higher temperature and humidity showing protective effects. These findings suggest that short-term environmental stressors disproportionately affect respiratory health in older adults and support future cross-country comparative analyses.